Sami (Lapland) reindeer herders, Woodland Park, 1898 - Wilse, Anders Beer, 1865-1949 (1898)
The Lapland-Yukon Relief Expedition spent two weeks in Seattle in March of 1898 before traveling on to Alaska. Here, two herders are depicted in Woodland Park. Stamped on verso: Wilse, Scenic Fotografer, McDonald Blk. 811 2nd Ave. Seattle, Wash. Handwritten on verso: Gift Ben Card 11-20-58 Caption on image: No. 567 Wilse & Kirk photo PH Coll 285.28 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number